Influence of the Euro Crisis on the Prospects of the European Single Market - Makrevska disoska, Elena (Economic Research Institute at the Bulgarian Academy of Sciences, 2015)
There is a growing concern about the future of the European Monetary Union (EMU) and the sustainability of the Euro. The worst case scenario: the break-up of the Single currency would not remain limited to the EMU itself, but would cause huge macroeconomic disruptions. Furthermore, if the countries reintroduce their national currencies, economically stronger countries will experience domestic currency appreciation towards the weaker economic counties. That would mean reduction of their exports, i.e. reduction of the price competitiveness. In such a situation, in order to protect their domestic economies, the countries will introduce protectionist measures which would suspend the Single market. Without the free movement of factors of production it is impossible for the Union to survive. This means that if the Eurozone falls apart, there will be a complete end to the Union. Returning back to the stages of regional integration as common market or customs union is theoretically impossible. Still, in any possible scenarios for how the Euro crisis might develop would adversely affect the Single market. Solving the macroeconomic imbalance of the Union will be a condition for its sustainability in the future and for insuring better future prospects of the Single Market.
Keywords: euro, Single Market